Recent advances in the application of artificial intelligence in age-related macular degeneration - Jian Xiong; Yunwei Hu; Guodong Li; Yundi Gao; Fen Xiong; Zidan Chen; Yucai Lin; Xinjing Xia; Yulan Yang (BMJ Open Ophthalmology)
Recent advancements in ophthalmology have been driven by the incorporation of artificial intelligence (AI), especially in diagnosing, monitoring treatment and predicting outcomes for age-related macular degeneration (AMD). AMD is a leading cause of irreversible vision loss worldwide, and its increasing prevalence among the ageing population presents a significant challenge for managing the disease. AI holds considerable promise in tackling this issue. This paper provides an overview of the latest developments in AI applications for AMD. However, current limitations include insufficient and unbalanced data, lack of interpretability in models, dependence on data quality and limited generality.